Comparison of the long-term results of bypass surgery versus below-the-knee angioplasty in infrapopliteal lesions that results in ulcer or toe gangrene - Mohammad Reza Kalantar Motamedi; Niki Tadayon; Babak Sabet; Younes Abdolalian (Indian Journal of Vascular and Endovascular Surgery, 2023)
Background and Aim: The optimal revascularization strategy for patients with severe leg ischemia remains uncertain. The purpose of this study was to compare outcomes of bypass surgery and angioplasty in isolated below-the-knee lesions. Methods: Patients with ulcers or toe gangrenes, undergone below-the-knee bypass surgery or angioplasty from January 2015 to December 2017, were included in the study. Amputation-free survival (AFS) and overall survival (OS) were assessed using the Kaplan–Meier and Cox regression tests. Results: Eighty-eight patients were included in this study, of which 43 underwent bypass surgery and 45 underwent endovascular interventions. The mean age in the bypass group was 73.1 (±7.1) years and 73.9 (±7.2) years in the angioplasty group. There were no significant differences in sex, diabetes, hypertension, history of smoking, history of stroke, and renal insufficiency between the two groups. AFS was 43.4 (±8.5) months in the bypass group and 39.8 (±8.9) months in the angioplasty group which was significantly better in the bypass group (P = 0.05). OS was 49.6 (±10.6) months in the bypass group and 46.2 (±11.7) months in the angioplasty group but did not differ statistically significant (P = 0.32). Conclusion: AFS was significantly higher in the bypass group. Thus, bypass surgery seems preferable to angioplasty for all patients with severe leg ischemia except those with multiple comorbidities and those whose vein is not adequate for bypass.